1996
DOI: 10.1007/bf01411056
|View full text |Cite
|
Sign up to set email alerts
|

A source of haemorrhage in adult patients with moyamoya disease: The significance of tributaries from the choroidal artery

Abstract: This study concerns 19 patients over 16 years of age with Moyamoya disease. Ten cases of intracranial haemorrhage, as the initial haemorrhagic event in patients aged from 21 to 55 (haemorrhagic group) and 9 cases of ischaemic events in 18- to 53-year-old patients (ischaemic group) were included. All haemorrhages were associated with intraventricular haemorrhages (IVH); and all but one case of thalamic haemorrhage were thought to be primary IVH (2 cases of small paraventricular haemorrhage; 2 of small haemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 13 publications
3
35
0
Order By: Relevance
“…As independent risk factors for hemorrhagic stroke in MMD, anterior choroidal artery and posterior communicating artery dilation or extension have been described. [5][6][7] Moreover, cerebral microbleeds in adult patients with MMD were reported to be probable predictors of subsequent hemorrhage, and dilation and extension of the anterior choroidal artery or posterior communicating artery were independent risk factors of cerebral microbleeds in deep and periventricular white matter. 11 In our study, fetal-type PCA development was more commonly observed in the hemorrhagic hemispheres than in the ischemic or control hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…As independent risk factors for hemorrhagic stroke in MMD, anterior choroidal artery and posterior communicating artery dilation or extension have been described. [5][6][7] Moreover, cerebral microbleeds in adult patients with MMD were reported to be probable predictors of subsequent hemorrhage, and dilation and extension of the anterior choroidal artery or posterior communicating artery were independent risk factors of cerebral microbleeds in deep and periventricular white matter. 11 In our study, fetal-type PCA development was more commonly observed in the hemorrhagic hemispheres than in the ischemic or control hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…1 The moyamoya vessels may rupture because of persistent hemodynamic stress, thus intracranial bleeding occurs in the basal ganglia, thalamus, and periventricular region. 2,3 According to recent studies, silent microbleeds are identified on T2*-weighted MRI in moyamoya disease. [4][5][6] They are found in the basal ganglia, thalamus, and periventricular region, where intracranial bleeding often occurs.…”
mentioning
confidence: 99%
“…The volume of intraparenchymal hemorrhage was measured. Because previous reports suggested a higher prevalence of anterior choroidal artery (AchA) dilatation in hemorrhagic MMD, 3 we assessed the status of the AchA in patients with MMD in whom angiographic analysis was available. Because the mean length of the AchA in normal subjects is 25 mm, 4 and an AchA 40 to 50 mm long was classified as "well visualized," 5 we defined any AchA >40 mm as "prominent AchA," which was assessed by an investigator blinded to the hemorrhage location.…”
Section: Methodsmentioning
confidence: 99%